Urgensi Adanya Akta Notaris Terkait Pendirian Perseroan Perseorangan Pasca Undang-Undang Nomor 6 Tahun 2023 Tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 Tentang Cipta Kerja Menjadi Undang-Undang - Dewi Masitah; Ermanto Fahamsyah; R.A. Rini Anggraini (Syntax Idea)
The concept of the Omnibus Law is not new for countries that adhere to the Common Law legal system, but it is new for Indonesian legislation. However, this is a new thing for legislation in Indonesia. This raises the Pros and Cons of Indonesian legal issues. The purpose of this article is to find out the juridical implications of establishing an individual company after the regulation in lieu of Law Number 2 of 2022 concerning Job Creation, to find out whether the establishment of an individual company without a notarial deed has provided legal protection for the legality of documents and the identity of the founder of an individual company as the sole shareholder. , and what are the legal remedies if there is a dispute over the permit certificate for an individual company if it was established without going through a notary. The research approach used is a statutory approach, a conceptual approach, and a historical approach. The data were obtained from three types of legal materials. The results of this study show that the legal status of an individual limited liability company in the legal system in Indonesia contradicts the regulations relating to limited liability companies that were already in effect before. The responsibility of the shareholders of an individual company suffers a loss, so the shareholder is responsible for the shares handed over to the individual company except for the shareholder. Government Regulation Number 8 of 2021 does not regulate what efforts the founders can take if there are risks or problems that occur in an Individual Limited Liability Company.